Thermal behaviour of LixMeO2 (Me = Co or Ni + Mn + Co) cathode materials. Issue 19 (25th April 2017) - Gotcu, Petronela; Pfleging, Wilhelm; Smyrek, Peter; Seifert, Hans J.
Abstract : Thermal behaviour and thermophysical properties of two typical cathodes for lithium-ion batteries were studied in dependence of temperature and lithiation degree. Abstract : Thermal behaviour and thermophysical properties of two typical cathodes for lithium-ion batteries were studied in dependence of temperature. The cathode materials are composite thick films containing a mixture of 90 wt% LiMeO2 active material (with Me = Co or Me = Ni + Mn + Co, respectively) and additives (binder and carbon black), deposited on aluminium current collector foils. The thermal conductivity of each cathode type and their corresponding composite layers were determined up to 573 K from the measured thermal diffusivity, the specific heat capacity and the estimated density based on metallographic methods and structural investigations. In addition, the impact of lithiation degree x in Li x MeO2 on the transport properties of cathode samples was also investigated. The quantitative determination and the homogeneity of Li content on the surface and within the bulk of the samples were validated by laser induced breakdown spectrometry. The results presented here explain at cell component level, i.e. cathode material, the thermal runaway behaviour of lithium-ion batteries in a combined approach of application oriented and fundamental research. Therefore, these data are significant for improving the simulation studies of their thermal management, in which the bulk properties are assumed, as a common approach, temperature and lithiation degree independent.